THE STUDENTS’ WRONG PRONOUN USAGES IN SIMPLE SENTENCE - Dedy Subandowo (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract:This papar entitled Students’ Wrong Pronoun Usages in Simple Sentence. The aim of this research is to know the types of students’ wrong pronoun usage in simple sentence, the most occurrence pronoun mistakes done by the students, and the factors influencing them. These research subjects were the students at the eleventh grade of SMA Kartikatama Metro. The sampling technique used in this research was purposive sampling. To check validity and reliability of the result the researcher used primery dataand triangulation, such as questioner sheet for the students and interview for the teacher. Therefore, the researcher analyzed the data with marking, noting, classifying, identifying, and analyzing the data.The results of the research are,first the types of wrong pronoun usage in simple sentencehappened in possessive pronoun. Second, the most common mistakes done by the students in pronoun usage are possessive pronoun. Third, the factors influencing them are internal and external factor. Keyword: Pronoun, Simple Sentence, Syntax